Reforming Public Child Welfare in Indiana, 2007-2009 - Folaron, Gail ([Verlag nicht ermittelbar], 2018)
The study of Indiana's Child Welfare reform was designed to identify community professionals' perceptions of the Department of Child Services (DCS) following the release of a pilot program to reform child welfare in the state of Indiana. In December, 2005, the pilot project was officially rolled out in three regions of the state. The three chosen regions of the state included 11 county agencies with both urban and rural population centers. Together these regions represented 28% of the state's CHINS (Child In Need of Service) population and 20% of the child fatalities for 2004. This study represents data collected to identify perceptions of the DCS by sending a survey to professionals in the 11 pilot and 12 comparison counties. The survey questions were arranged by categories of safety, permanency, well-being, DCS goals, the reform, team meetings, and demographics. Nine separate instruments were developed and disseminated for each community group. The community professionals surveyed included: Court Appointed Special Advocates (CASAs), foster parents, judges, Law Enforcement Agencies (LEAs), medical and public health professionals, schools, social service professionals, and mental health professionals. Survey instruments were tailored to each audience, with questions that were derived from the DCS "Framework for Individualized Needs-Based Child Welfare Service Provisions," which outlined the agency's core practice values and principles.